The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1980-57642013dn70100005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frontotemporal dementia in community-based studies in Latin America: A systematic review

Abstract: Latin America (LA) is experiencing a rise in the elderly population and a consequent increase in geriatric problems such as dementia. There are few epidemiological studies assessing the magnitude of dementia and dementia subtypes in LA.OBJECTIVETo identify published community-based studies on the prevalence of FTD in LA countries.METHODSA database search for door-to-door studies on FTD prevalence in LA was performed. The search was carried out on Medline, Embase, and LILACS databases for research conducted bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
(37 reference statements)
2
13
1
6
Order By: Relevance
“…Community-based studies conducted in LA with individuals aged ≥55 years have found that the prevalence of FTD ranges from 12 to 18 cases per 1000 people, and that it is higher among Brazilians (2.6%–2.8%; Herrera et al, 2002 ; Lopes, 2006 ) than among Peruvians (1.90%; Custodio et al, 2008 ) and Venezuelans (1.53%; Maestre et al, 2002 ; Table 2 ). The values reported are intermediate with respect to global studies (Custodio et al, 2013 ). In general, the exact prevalence of FTD is unknown.…”
Section: The Prevalence Of Dementia In Latin Americacontrasting
confidence: 77%
“…Community-based studies conducted in LA with individuals aged ≥55 years have found that the prevalence of FTD ranges from 12 to 18 cases per 1000 people, and that it is higher among Brazilians (2.6%–2.8%; Herrera et al, 2002 ; Lopes, 2006 ) than among Peruvians (1.90%; Custodio et al, 2008 ) and Venezuelans (1.53%; Maestre et al, 2002 ; Table 2 ). The values reported are intermediate with respect to global studies (Custodio et al, 2013 ). In general, the exact prevalence of FTD is unknown.…”
Section: The Prevalence Of Dementia In Latin Americacontrasting
confidence: 77%
“…Most of the literature available on the epidemiology of dementia comes from North American and European cohorts. The most extensive studies on the prevalence of dementia in LAC countries identified frequency rates similar to those reported by western and eastern countries ( 11 13 ). Among neurodegenerative dementia, Alzheimer's disease dementia (ADD) and Lewy body dementia are the leading cause of dementia, following by Frontotemporal dementia (FTD), the third most common form of dementia across all age groups, after, and is a leading cause of early-onset dementia ( 14 , 15 ), with a prevalence ranging from 3 to 26% described in North America and European populations ( 16 , 17 ).…”
Section: Introductionsupporting
confidence: 60%
“…Además, a diferencia de los países desarrollados los costos son originados predominantemente por los costos de los cuidados informales 1 , los costos médicos representan un pequeño porcentaje y los costos cubiertos por el sistema de salud son inexistentes 1,6 . En nuestro país, la demencia más frecuente en individuos mayores de 65 años es la enfermedad de Alzheimer (EA) (56,3%) 7 ; mientras que demencia frontotemporal (DFT) alcanza solamente el 1,90% 7,8 .…”
Section: Introductionunclassified